2001
DOI: 10.1093/alcalc/36.6.556
|View full text |Cite
|
Sign up to set email alerts
|

CORRELATION BETWEEN INHIBITION, WORKING MEMORY AND DELIMITED FRONTAL AREA BLOOD FLOW MEASURED BY 99mTc-BICISATE SPECT IN ALCOHOL-DEPENDENT PATIENTS

Abstract: Recently detoxified non-neurological alcoholic patients appear to be impaired in cognitive tasks measuring inhibitory processes as well as working memory (involving storage and manipulation of information). The aim of this study was to investigate in alcoholic participants the relationship between these two cognitive functions and regional cerebral blood flow (rCBF) studied at rest in regions of interest selected on the basis of recent PET studies which explored inhibitory and working memory in normal subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
46
2
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 40 publications
4
46
2
2
Order By: Relevance
“…Nevertheless, relationships between brain function deficits and neuropsychological impairments have been previously reported in neurologically normal alcoholdependent subjects (Adams et al, 1993;Dao-Castellana et al, 1998;Noel et al, 2001a). For example, Dao-Castellana et al (1998) observed in a PET study a significant relationship between the extent of left dorsolateral and medial prefrontal hypometabolism and lower reaction times in the Stroop test and lower verbal fluency performance.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nevertheless, relationships between brain function deficits and neuropsychological impairments have been previously reported in neurologically normal alcoholdependent subjects (Adams et al, 1993;Dao-Castellana et al, 1998;Noel et al, 2001a). For example, Dao-Castellana et al (1998) observed in a PET study a significant relationship between the extent of left dorsolateral and medial prefrontal hypometabolism and lower reaction times in the Stroop test and lower verbal fluency performance.…”
Section: Introductionmentioning
confidence: 96%
“…The selective alteration of executive functions, such as planning or problem solving, has been reported even in neurologically normal alcoholic patients (Oscar-Berman et al, 1997). The signs of cognitive dysfunction may occur up to 10 years before alcohol-related neurological disorders appear (Tuck and Jackson, 1991), and it has been suggested that chronic alcohol consumption may lead to early effects on cognitive operations that critically rely on frontal lobe function (Adams et al, 1993;Noel et al, 2001a).…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol-dependence has been associated with memory compromise, a compromise that has been observed for working memory [1][2][3][4][5], for memory for verbal or nonverbal stimuli [6][7][8], and for source memory, i.e., the ability to remember the context in which an event occurred [9,10]. Interestingly, autobiographical memory, or memory for personal experiences, has been also found to be compromised in alcohol-dependence.…”
Section: Introductionmentioning
confidence: 99%
“…There were also found deficits in the executive functions (behavioral inhibition) and in working memory, which is related to a system involving the short-term memory, responsible for the maintenance and manipulation of information in the mind for the accomplishment of complex cognitive tasks. 2 The alterations found in alcohol-dependent subjects seem to represent diffuse brain damage and although they improve substantially during withdrawal, some deficits remain even years after the last alcohol ingestion. 11 Subjects who use chronically alcohol, although being neurologically asymptomatic, may present dysfunctions in prefrontal lobe areas 12 ( Figure 1), implying neuropsychological deficits in verbal fluency (expressive language) and in inhibitory control (difficulty to suppress habitual and automatic responses instead of more elaborated competitive behaviors).…”
mentioning
confidence: 99%
“…3 11 Besides, patients with cognitive and neuroimaging alterations, mainly in frontal brain regions, tend to have a worse prognosis, associated with a higher number of relapses during treatment. 20 One study by Noël et al 2 assessed 20 alcohol-dependent subjects, comparing them to 20 normal volunteers, in exams which included neuropsychological tests, involving the functions of inhibitory control, working memory, abstraction capability and verbal memory, as well as analysis of brain function through SPECT. Patients were at the end of a detoxification program, with a mean of 18.8 days of withdrawal.…”
mentioning
confidence: 99%